Parasitosis y riesgos sanitarios de una especie exótica, Myiopsitta monachus: una revisión - Muñoz San Miguel, Ana Cristina (2025)
The monk parakeet (Myiopsitta monachus) is a high-risk invasive species worldwide, so the introduction of its pathogens increases the risk of infection and transmission in native species. The aim of this work was to collect information from documents published between 2000 and 2021 on the presence of ecto- and endoparasites of veterinary and public health interest reported in M. monachus. Only 13 documents were recorded (11 scientific articles and two from the grey literature), in which 17 species of parasites are reported (11 ectoparasites and six endoparasites). Ectoparasites had a higher prevalence (27.2 ± 30.8%) than endoparasites (16.0 ± 15.2%). The prevalence of ectoparasites and endoparasites was not influenced by environmental conditions (Ectoparasites: relative humidity: p>0.05; temperature: p>0.05; Endoparasites: relative humidity: p>0.05; temperature: p>0.05). Although there were no significant differences for each habitat type (temperate forest: p>0.05; scrubland: p>0.05), it is of great importance to raise awareness and develop control strategies for invasive species, since they pose a threat to animal and human health; however, the lack of information on the diseases that these species can present is an obstacle to understanding the risks they entail. This study showed that there are few reports of parasitic agents involving M. monachus.